2010
DOI: 10.1063/1.3481372
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive ZnO grown by pulsed laser deposition in pure Ar

Abstract: Ga-doped ZnO was deposited by pulsed laser deposition at 200 °C on SiO2/Si, Al2O3, or quartz in 10 mTorr of pure Ar. The as-grown, bulk resistivity at 300 K is 1.8×10−4 Ω cm, three-times lower than that of films deposited at 200 °C in 10 mTorr of O2 followed by an anneal at 400 °C in forming gas. Furthermore, depth uniformity of the electrical properties is much improved. Mobility analysis shows that this excellent resistivity is mostly due to an increase in donor concentration, rather than a decrease in accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 8 publications
4
31
0
Order By: Relevance
“…7 This confirms the robust character and repeatability in the PLD growth of Ga-doped ZnO in Ar at 200 C. Also, in the earlier studies, 6,10 we found from secondary-ion mass spectroscopy (SIMS) that N D % [Ga], showing that most of the Ga atoms reside on Zn sites, as donors, and that other impurity-or defect-related donors are not significant. More importantly, in Ref.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…7 This confirms the robust character and repeatability in the PLD growth of Ga-doped ZnO in Ar at 200 C. Also, in the earlier studies, 6,10 we found from secondary-ion mass spectroscopy (SIMS) that N D % [Ga], showing that most of the Ga atoms reside on Zn sites, as donors, and that other impurity-or defect-related donors are not significant. More importantly, in Ref.…”
supporting
confidence: 60%
“…We have previously shown that the growth of ZnO by PLD at 200 C in pure Ar produces material of very high conductivity. 7 Although PLD growth of ZnO in high partial pressures of H 2 is not common, the group at Pacific Northwest National Laboratories has used it in the past. 8,9 Unfortunately, an equipment malfunction occurred during the 100/0 growth, so this sample could not be easily compared to the other three.…”
mentioning
confidence: 99%
“…Under the logical assumption that the boundary-scattering-limited mean free path (mfp) should increase as d increases, we postulate that mfp = d/C, where C is a constant that depends on the particular system being studied [4,12]. The relevant velocity for scattering should be the Fermi velocity, so the mobility becomes:…”
Section: Theorymentioning
confidence: 99%
“…The resistivity of the films was sharply decreased after thermal treatments. This was an expected result mainly due to the increase of grain size and of structural homogeneity and to the reduction of scattering of carriers at the grain boundaries with annealing temperature but can also be connected to the decrease of excess oxygen and/or to the increase of oxygen vacancies (which in turn leads to an increase of the carrier concentration) [28,29]. Additionally, the dopants depletion from the SnO 2 lattice and subsequent clusterization at the grain boundaries can also contribute for decreasing the resistivity of the film since the ionic metals can act as trapping centers.…”
Section: Electrical Propertiesmentioning
confidence: 97%